Aluminum resistance of malting barley - O. V. Yakovleva (Труды по прикладной ботанике, генетике и селекции)
Background. Barley is the second cereal crop in Russia in terms of its importance and production volume. It is used for food, feed, and industrial purposes. The production of malting barley in Russia exceeds 1.5 million tons; each year the area under this crop increases by 10–15%, reaching 600,000– 800,000 hectares. Barleys suitable for brewing must have certain physicochemical and technological properties. The main requirements for raw materials are presented in GOST 5060-86 (state standard for malting barley). An important condition for obtaining sustainable harvests is the development and utilization of cultivars resistant to a set of edaphic stressors. The purpose of this work was searching for resistant cultivars for use in targeted breeding.Materials and methods. The material for the study included 161 spring barley cultivars for brewing from the collection of plant genetic resources held by VIR. The laboratory assessment of aluminum tolerance in barley accessions was carried out at the initial phases of plant growth and development, using the method of calculating root and shoot length indices. The tested malting barley was classified into five resistance groups.Results and conclusions. Cultivars resistant to Al3+ ions were identified among different ecogeographic groups of malting barleys. The trait had a wide range of variability in terms of both the root length index (0.17–0.95) and shoot length index (0.47–0.99). Accessions with high resistance to ionic (Al3+) stress can be used in barley breeding targeted at the development of high-yielding malting cultivars most adapted to harmful environmental factors.